USM STRENGTHENS COLLABORATION WITH INDIAN COMPANY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KARNATAKA, INDIA, 16 November 2016 Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail today begins her official educational visit to India by holding a discussion session with Aurigene Discovery Technologies Limited key executives headed by its CEO, Mr. Chavali S.N. Murthy.